2010
DOI: 10.1016/j.bone.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell-derived CD34+ cells function as MSC progenitor cells

Abstract: Mesenchymal stem/stromal cells (MSCs) have been isolated from various tissues and utilized for an expanding number of therapies. The developmental pathways involved in producing MSCs, and the phenotypic precursor/progenitor cells that give rise to human MSCs remain poorly defined. Human embryonic stem cells (hESCs) have the capability to generate functional hemato-endothelial cells and other mesoderm lineage cells. hESC-derived CD73 + cells have been isolated and found to have similar phenotypic and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 54 publications
(67 reference statements)
7
59
0
Order By: Relevance
“…In contrast, H1-MSCs, WA1-MSCs, and BM-MSCs express MSC surface markers yet H1-MSCs andWA1-MSCs express a lower level of CD106 compared to BM-MSCs. Similar findings demonstrating that ESC-MSCs express low levels of MSC markers, CD105 and CD106, have been reported (Hwang et al 2008a, b; Kopher et al 2010). Additionally, CD106 has been shown to be associated with the multi-lineage differentiation potential of adult tissue-derived MSCs, as the expression level of CD106 decreases with progression of differentiation (Liu et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, H1-MSCs, WA1-MSCs, and BM-MSCs express MSC surface markers yet H1-MSCs andWA1-MSCs express a lower level of CD106 compared to BM-MSCs. Similar findings demonstrating that ESC-MSCs express low levels of MSC markers, CD105 and CD106, have been reported (Hwang et al 2008a, b; Kopher et al 2010). Additionally, CD106 has been shown to be associated with the multi-lineage differentiation potential of adult tissue-derived MSCs, as the expression level of CD106 decreases with progression of differentiation (Liu et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Recently, Kopher et al demonstrated that hESC-derived CD34 Ï© endothelial precursors have phenotypic and functional features similar to MSCs. 38 Therefore, Ang1-EC-ESCs may contain MSC components. When Ang1-ECESCs were plated on a 0.1% gelatin-coated dish in EGM-2 medium, they showed a typical cobblestone-like appearance as early as 6 hours from the start of incubation ( Figure 6A).…”
Section: Ang1-induced Ecs Have a Neovasculogenic Potential In Vitro Amentioning
confidence: 99%
“…+ cells as precursors of human (Kopher et al, 2010) and murine (Kaiser et al, 2007) MSC. Interestingly, the CD34 expression in long-term MSC culture was observed , in addition to report demonstrating higher angiogenic potential of CD34 + subpopulation of MSC (Copland et al, 2008), what is altogether consistent with our study.…”
Section: Cd34mentioning
confidence: 99%